Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/mop.26566
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a narrow microwave carrier from a bimodal fiber laser

Abstract: band-pass filter are obtained as shown in Figure 5(a). Obviously, the band-pass filter behaves well in the pass-band of which the return loss is below À10 dB (from 4.66 to 5.55 GHz). The outband suppression is almost better than 20 dB. The simulated resonant characteristics of the three-cascaded CSRR band-pass filter are obtained as shown in Figure 5(b). As can be seen from Figure 5(b), the return loss of the three-cascaded CSRR bandpass filter throughout pass-band range is below À18 dB, whereas out-band suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…We employ a fiber ring laser configuration very similar to that reported in Reference8 but with a mutual coupling from an OEO loop. It was shown that the present configuration was able to narrowing the microwave FWHM linewidth by 84.1% when compared with that reported in Reference8. Note that the phase‐noise of −100 dBc/Hz @10 kHz is very close to that achieved by OEO architectures that do not use kilometer‐long fibers and have high integrability 17,18 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We employ a fiber ring laser configuration very similar to that reported in Reference8 but with a mutual coupling from an OEO loop. It was shown that the present configuration was able to narrowing the microwave FWHM linewidth by 84.1% when compared with that reported in Reference8. Note that the phase‐noise of −100 dBc/Hz @10 kHz is very close to that achieved by OEO architectures that do not use kilometer‐long fibers and have high integrability 17,18 …”
Section: Resultsmentioning
confidence: 99%
“…This is accomplished in a ring topology, where an erbium‐doped fiber amplifier (EDFA) act as a broadband light source while a second optical amplifier works as a gain media. A similar DWFRL experimental configuration has been reported in Reference8, but without the opto‐electronic oscillator (OEO) feedback loop. When compared with Reference8, the present novel setup allows a linewidth reduction of ~84.1% at full width at half maximum (FWHM) of the microwave carrier generated from the beat of the optical signals.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…An arrangement of two similar in‐tandem FBGs gives origin to an all‐fiber FP cavity with narrow transmittance peaks appearing patterned inside the resonance band of the FBGs . The main FP cavity of the proposed sensor is obtained by placing two similar FBGs spaced by a physical distance d from each other, as depicted in Figure (a), the FBGs acting as spectrally‐selective partially‐reflective mirrors.…”
Section: Modeling the Devicementioning
confidence: 99%
“…Optical fiber sensing can deliver numerous key advantages over conventional, electronic sensing technologies for design validation, process optimization, and condition monitoring. The development in the field of fiber laser over the past years has been very aggressive with number of reports being published on new configuration and setting that has improved the performance of the fiber laser in term of new configuration and setting to produce higher output power, larger tuning range, and more output lasing channels [1–5]. This has attracted many researchers to find ways to develop a new application that will fully use the performance of the fiber laser.…”
Section: Introductionmentioning
confidence: 99%